From: Alexander Krauss <krauss@in.tum.de>
Zhang Hong wrote:
Generalize your lemma first:
lemma "m <= n --> elems m (ua(n:=uc)) = elems m ua"
Unlike the original, you can easily prove this by induction on m. (This
is because you get a stronger induction hypothesis here...)
Hope this helps.
Alex
From: Zhang Hong <hong@ercist.iscas.ac.cn>
Hello,
I have an questions pertinent to the natural numbers type.
Given the following definition:
--"translate an array into a natural list "
consts
elems :: "nat => (nat => nat) => nat list"
primrec
"elems 0 arr = []"
"elems (Suc n) arr = (arr n) # elems n arr"
Question:
Can someone please explain how can I prove the following lemma?
lemma "\<forall>ua uc. elems n (ua(n:=uc)) = elems n ua"
Thanks,
Hong Zhang.
Last updated: Nov 21 2024 at 12:39 UTC